Analisis Faktor Pendorong Filipina Melanjutkan Kembali Visiting Forces Agreement (VFA) dengan Amerika Serikat Pada Masa Duterte (2020-2021) - Christina, Ni Ketut Sara; Priadarsini, Ni Wayan Rainy; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 1 (2023): JURNAL DIKSHI, 2023)
This research discusses what are the advocate factors for the Philippines to resume the Visiting Forces Agreement (VFA) with the United States during the Duterte period in 2020-2021. In February 2020 Duterte issued a statement discontinuing the VFA which was a troop visit agreement that allowed rotation of the US troop presence in the Philippines and later decided to resume the agreement. The researcher uses the concept of Foreign Policy Decision Making by William D. Coplin which mentions three determinant factors that influence the decision-making process, that is domestic political conditions, economic and military capabilities, and international context. The researcher found that Duterte's decision to resume VFA was influenced by these three factors.